THE USE OF CLUSTERING TEHNIQUE TO TEACH WRITING IN DESCRIPTIVE TEXT - Oskar Dirta Ariloka (FPB PBI 16 UMY 006, 2016)
Writing is usually considered as the most difficult skill to master for the students who are learning English. It has many complex processes such as prewriting, drafting, editing, and revising. Writing is often influenced by the constraint of genre. One of the genres is descriptive text. In fact, the writer found some problems in conveying the English material to the students. An effort done to solve the problem is by using clustering. Clustering, visual way of prewriting, can help the students to organize their thoughts. The purposes of this study were (1) to find out the effectiveness of clustering in writing ability of descriptive text, (2) to find out the effectiveness of guiding question in writing ability of writing descriptive text, (3) to explain to what extent the interaction of teaching technique (clustering and guiding questions) to the students’ writing ability at the tenth grade of SMK Wisudha Karya Kudus is. This study was an experimental research that conducted in 2 classrooms containing 41 students in experimental group and 40 students in control group as the subjects of the study. The experimental group was taught by using clustering. Meanwhile, the control group was taught using guiding questions which is the way of coming up with a topic uses journalist’ question such as who, what, where, when, why, and how. The instrument used to collect the data was written test. This study found that the score of writing descriptive text taught by using clustering had mean 67.2 which was catagorized as average. The results of the research revealed that students taught by clustering in teaching writing descriptive text had the t-value 2.663 > t-table 1.990 with the significance level of 0.05, so the null hypothesis (Ho) is rejected. It means that there is a significant difference between the ability in writing descriptive text of the tenth grade students of SMK Wisudha Karya Kudus in academic year 2015/2016 taught by using clustering and using guiding questions.